Islamic education management: Integration of science, arts, and professions in optimizing the education system - Damri, Damri; Irawadi, Hermen; Elvarisna, Elvarisna; Sari, Rahmi; Hidayat, Rahmad (Institute of Accounting Research and Novation (IARN), 2024)
This study aims to explore Islamic education management through the integration of science, art, and profession in order to optimize the education system. A holistic approach that combines these three elements is expected to improve the quality of education and the relevance of the curriculum in Islamic educational institutions. By using This research is a qualitative research with a library research approach. Data Analysis using qualitative data analysis techniques, including data coding and categorization, to find the main themes related to the integration of science, art, and profession in Islamic education, this study analyzes best practices in implementing the integration of science, art, and profession in the education system. The results show that the integrative approach not only increases students' learning motivation, but also forms characters that are in accordance with Islamic values. This study recommends the development of a more flexible and collaborative curriculum, as well as the need for training for educators to implement the integration effectively. This study reveals that Islamic education management that integrates science, art, and profession has great potential to optimize the education system. Collaboration is needed between various parties to design a relevant curriculum and training for educators to be able to implement the integration effectively. Thus, Islamic education can produce a generation that is not only knowledgeable, but also has character and is ready to contribute to society.